69.6k views
1 vote
I wanna know the answer -4(2p+5)=3(6p-11)

2 Answers

4 votes

Answer:

P= 1/2

Explanation:

First distribute over multiplying. -4 * 2p is -8p, -4 * 5 is -20. Now you do this on the other side, so 3 * 6p is 18p, and 3 * -11 is -33.

Now, your equation is -8p-20= 18p-33. Add 8p to both sides

Now you have -20=26p-33. Add 33 to both sides.

Almost done! You now have -13=26p. Divide both sides by 26. Now you have your answer, which is P=12

5 votes

Answer: the answer is

Explanation:

I wanna know the answer -4(2p+5)=3(6p-11)-example-1
User Jdhao
by
4.5k points